Financial inclusion in rural Uganda: The role of social capital and generational values - George Okello Candiya Bongomin; John C. Munene; Joseph Ntayi Mpeera; Charles Malinga Akol (Cogent Business & Management, 2017)
The purpose of this paper was to examine how variations in social capital across generations promote financial inclusion among the poor in rural Uganda. Data were collected from a sample of 200 poor households located in Mukono district and processed using ordinary least square regression and ANOVA to examine how variations in social capital across generations promote financial inclusion of the poor in rural Uganda. The results generated indicate that variations in social capital components across generations significantly and positively affect financial inclusion of the poor in rural Uganda. The paper makes a significant contribution to existing body of literature by showing that variations in social capital across generations can cause an effect in financial inclusion of the poor, especially in rural Uganda. Managers of financial institutions should consider generational values in promoting financial inclusion. Specifically, they should design social financial products and services that can boost collective action in order to promote financial inclusion of the poor, especially in rural Uganda.
Keywords: 650